A pilot study of participatory video in early psychosis: Qualitative findings - Arlene G. MacDougall; Elizabeth Price; Sarah Glen; Joshua C. Wiener; Sahana Kukan; Laura Powe; Richelle Bird; Paul H. Lysaker; Kelly K. Anderson; Ross M.G. Norman (Qualitative Research in Medicine & Healthcare)
For people with psychotic disorders, developing a personal narrative about one’s experiences with psychosis can help promote recovery. This pilot study examined participants’ reactions to and experiences of participatory video as an intervention to help facilitate recovery-oriented narrative development in early psychosis. Outpatients of an early psychosis intervention program were recruited to participate in workshops producing short documentary-style videos of their collective and individual experiences. Six male participants completed the program and took part in a focus group upon completion and in an individual semistructured interview three months later. Themes were identified from the focus group and interviews and then summarized for descriptive purposes. Prominent themes included impacts of the videos on the participants and perceived impacts on others, fulfilment from sharing experiences and expressing oneself, value of collaboration and cohesion in a group, acquiring interpersonal and technological skills, and recommendations for future implementation. Findings of this study suggest that participatory video is an engaging means of self-definition and self-expression among young people in recovery from early psychosis.